The correlation of ABC goal attainment with insulin resistance/sensitivity in Syrian type 2 diabetes patients - Samer Younes (Diabetes Epidemiology and Management, 2024)
Background: The rising prevalence of type 2 diabetes (T2D) in Syria emphasizes the urgent requirement for effective management approaches. The ABC goals, which include maintaining glycated hemoglobin levels below 7 %, blood pressure below 140/90 mmHg, and low-density lipoprotein cholesterol levels below 100 mg/dl, serve as crucial benchmarks for managing T2D and its associated comorbidities. Methods: In this cross-sectional study, the achievement of ABC goals was retrospectively examined among 681 clinically diagnosed T2D patients (not on Insulin) who participated in a six-year online lifestyle intervention program for diabetes management at the Freedom from Diabetes Clinic in Syria between January 2016 and December 2022. Results: Out of the participants, 152 (22.3 %) successfully achieved all three ABC goals, while 306 (45.0 %) and 183 (26.9 %) achieved two or one goal(s) respectively. The factors influencing the attainment of all three ABC goals revealed a significant association with older age (>50 years), lower body mass index (<25 kg/m2), and lower insulin resistance (Homeostatic Model Assessment of Insulin Resistance < 2.5). Furthermore, patients who successfully achieved all three ABC goals exhibited lower insulin resistance, improved lipid profiles, and higher insulin sensitivity and beta cell function. Conclusion: This study offers new insights into the relationship between insulin resistance/sensitivity and the achievement of ABC goals in the Syrian population with T2D, underscoring the necessity for tailored strategies to enhance comprehensive diabetes management.